Optimization of Ethanol Concentration in the Extraction of Basil Leaves (Ocimum sanctum L.) on Total Phenolic Content, Total Flavonoid Content, and α‑Amylase Enzyme Inhibitory Activity - Danang Raharjo; Inanda Raharjo; Vivin Marwiyati Rohmana (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Type 2 diabetes mellitus is a global health problem that requires effective blood glucose control strategies, one of which is through the inhibition of the α-amylase enzyme to prevent postprandial hyperglycemia. This study aimed to analyze the effect of varying ethanol concentrations (50%, 70%, 96%) as a solvent on the extraction efficiency of bioactive compounds from basil leaves and their α-amylase enzyme inhibitory activity. Extraction was carried out using the maceration method, and the obtained extracts were analyzed for total phenolic content (TPC) using the Folin-Ciocalteu method, total flavonoid content (TFC) with AlCl₃ reagent, and α-amylase inhibitory activity using the iodine method. The results showed that ethanol concentration significantly influenced all tested parameters. The 70% ethanol extract yielded the highest TPC (108.441 ± 0.495 mg GAE/g), the highest TFC (70.535 ± 0.393 mg QE/g), and the strongest α-amylase inhibitory activity (IC₅₀ 49.255 µg/mL). A strong positive correlation was observed between the increase in phenolic and flavonoid compound levels and the enhancement of enzyme inhibitory activity. These results indicate that 70% ethanol is the optimal solvent for extracting antidiabetic compounds from basil leaves, which function by inhibiting key carbohydrate-digesting enzymes. The resulting basil leaf extract has the potential to be developed as an adjuvant therapeutic agent for the management of type 2 diabetes mellitus.